2016
DOI: 10.3390/medicines3040031
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Cytotoxic Investigation of Flacourtin from Oncoba spinosa

Abstract: Background: Oncoba spinosa, an endangered medicinal plant whose secondary metabolites have not been extensively profiled, and which is hitherto yet to be examined for cytotoxicity, is being investigated in this study. Methods: Leaves of Oncoba spinosa (800 g) were extracted with 95% aqueous methanol. The crude extract was partitioned with n-hexane and the resultant defatted extract was extensively chromatographed on silica gel to yield compound 1 which was subjected to spectroscopic analysis. A brine shrimps l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Ethnopharmacological data has revealed that OS has been extensively used for the treatment of diabetes and cancer in Nigeria region [5]; leaves and roots are used in African countries for the treatment of urethral discharges, infertility, epilepsy, dysentery and bladder conditions [6][7][8]; fruits are used for the treatment of syphilis, wounds, parasitic worms, and sexual impotence [9]. α-glucosidase inhibitory, radical scavenging and cytotoxicity activities of OS leaves have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Ethnopharmacological data has revealed that OS has been extensively used for the treatment of diabetes and cancer in Nigeria region [5]; leaves and roots are used in African countries for the treatment of urethral discharges, infertility, epilepsy, dysentery and bladder conditions [6][7][8]; fruits are used for the treatment of syphilis, wounds, parasitic worms, and sexual impotence [9]. α-glucosidase inhibitory, radical scavenging and cytotoxicity activities of OS leaves have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Balogun et al examine an endangered medicinal plant, Oncoba spinosa . This small tree grows in many areas of Africa [ 16 ]. The fruit is used in Traditional Healing in Nigeria.…”
mentioning
confidence: 99%